2017
DOI: 10.1093/hmg/ddx101
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XIII secures pre- and postsynaptic integrity of the neuromuscular synapse

Abstract: Both transmembrane and extracellular cues, one of which is collagen XIII, regulate the formation and function of the neuromuscular synapse, and their absence results in myasthenia. We show that the phenotypical changes in collagen XIII knock-out mice are milder than symptoms in human patients, but the Col13a1-/- mice recapitulate major muscle findings of congenital myasthenic syndrome type 19 and serve as a disease model. In the lack of collagen XIII neuromuscular synapses do not reach full size, alignment, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 37 publications
8
60
0
1
Order By: Relevance
“…Due to the highly increased protein expression, especially in the diaphragm and EDL muscles of the Col13a1 oe mice, we expected to find an increased accumulation of collagen XIII at the NMJs. Spots of collagen XIII were located in the AChR‐positive areas of the NMJs in the wild‐type muscles (Figure a–c), as previously shown (Härönen et al., ; Latvanlehto et al., ). Collagen XIII immunoreactivity in the Col13a1 oe mice was for the most part comparable to that in the wild‐type controls in the postsynaptic areas of all the muscles studied (Figure a–c), but somewhat surprisingly, we could also detect NMJs without collagen XIII immunoreactivity in the Col13a1 oe mice, pronounced in the diaphragm (Figure a, asterisk).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Due to the highly increased protein expression, especially in the diaphragm and EDL muscles of the Col13a1 oe mice, we expected to find an increased accumulation of collagen XIII at the NMJs. Spots of collagen XIII were located in the AChR‐positive areas of the NMJs in the wild‐type muscles (Figure a–c), as previously shown (Härönen et al., ; Latvanlehto et al., ). Collagen XIII immunoreactivity in the Col13a1 oe mice was for the most part comparable to that in the wild‐type controls in the postsynaptic areas of all the muscles studied (Figure a–c), but somewhat surprisingly, we could also detect NMJs without collagen XIII immunoreactivity in the Col13a1 oe mice, pronounced in the diaphragm (Figure a, asterisk).…”
Section: Resultssupporting
confidence: 85%
“…This suggest that the AChR clusters in the diaphragm of Col13a1 oe mice are indeed simpler than control clusters, but in the soleus and EDL, the morphology of the NMJ is similar to that in the controls and only the size of the AChR clusters is reduced. The delayed and incomplete maturation of the AChR clusters in the Col13a1 oe mice resembles the phenotype previously found in collagen XIII knockout mice (Härönen et al., ; Latvanlehto et al., ).…”
Section: Resultssupporting
confidence: 82%
“…The present data provide information highly relevant in view of the reported occurrence and functional significance of collagen XIII in mouse models and human CMS . In addition, our recent studies suggested that collagen XIII is located at the functional unit of the NMJ, binds acetylcholinesterase‐associated collagen (ColQ), and contributes to the distribution pattern of acetylcholine esterase at the NMJ . Therefore, we speculate that a putative pathogenic mechanism of collagen XIII autoantibodies may be hindering the interaction between collagen XIII and other synaptic basal lamina components and, consequently, destabilizing the neuromuscular synapse.…”
Section: Discussionmentioning
confidence: 60%
“…Our patient has a novel homozygous c.739C>T; p.Arg 247* mutation (NM_001130103.1) of COL13A1 , a large gene encoding nonfibrillar transmembrane collagen, which is concentrated on the postsynaptic junctional folds from where its ectodomain can be cleaved and shed into the synaptic cleft. Collagen type XIII α1 chain binds directly to the collagen‐like tail subunit of AChE . Its function is essential for the correct assembly of the presynaptic, synaptic, and postsynaptic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen type XIII α1 chain promotes synaptic development and maturation as well as regeneration after peripheral nerve injury . COL13A1 −/− mice have small nerve terminals, decreased neurotransmitter release, and decreased postsynaptic AChR clustering …”
Section: Discussionmentioning
confidence: 99%